Corporate Social Responsibility in Islamic Banking: A Practical Evaluation - Farhan, Muhammad; Soediro, Achmad; Kusumawardani, Media; Adhitama, Fardinant; Lakilaki, Eogenie (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
The objective of this study is to investigate how the CSR framework adopted by Islamic banks conforms to Islamic principles by integrating the values of Maqasid al-Sharia. This study adopts a qualitative approach to examine the alignment of CSR systems implemented by Islamic banks with Islamic principles, specifically incorporating the values of Maqasid al-Sharia. In this research, thematic analysis is used as a research strategy and data analysis method. Data was obtained through direct interviews with employees from the CSR departments of Bank Sumselbabel Syariah, Bank Syariah Indonesia, and Bank Muamalat. It can be concluded that Bank Syariah Indonesia (BSI) exhibits a robust dedication to the principles of Islamic finance, demonstrated through its financial reporting practices and business operations that steer clear of elements like riba (usury) and gharar (excessive uncertainty).